Family History in Periodic Fever, Aphthous Stomatitis, Pharyngitis, Adenitis (PFAPA) Syndrome - Manthiram, Kalpana; Nesbitt, Emily; Morgan, Thomas; Edwards, Kathryn M (Pediatrics (Evanston), 2016)
The goal of this study was to describe family history and inheritance patterns in patients with periodic fever, aphthous stomatitis, pharyngitis, cervical adenitis (PFAPA) syndrome. We performed a case-control study to compare the family histories of patients with PFAPA recruited from Vanderbilt University Medical Center and matched healthy control subjects from a pediatric primary care practice in Nashville, Tennessee, by using a structured questionnaire. Characteristics of paired case subjects, control subjects, and their family members were compared by using McNemar's test and Wilcoxon signed-rank tests. Eighty PFAPA index case subjects and 80 control subjects were recruited. Eighteen PFAPA case subjects (23%) had ≥1 family member with PFAPA. Parents of PFAPA index case subjects were more likely to have recurrent pharyngitis (36% vs 16%; P < .001) and recurrent aphthous stomatitis (46% vs 28%; P = .002) compared with parents of control subjects. Siblings of case subjects had a higher prevalence of PFAPA (10% vs 2%; P = .04), recurrent pharyngitis (24% vs 10%; P = .03), and recurrent aphthous stomatitis (27% vs 7%; P = .003) compared with siblings of control subjects. A portion of PFAPA case subjects seems to be familial, implying an inherited genetic predisposition to the disorder and/or shared environmental exposures. First-degree relatives (parents and siblings) of patients with PFAPA have a higher prevalence of recurrent pharyngitis and aphthous stomatitis than relatives of control subjects, which suggests that these disorders represent reduced penetrance phenotypes of PFAPA. Further characterization of the genetics and inflammatory profiles of these patients and their relatives is warranted.